TUMPANG TINDIH REGULASI DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH NAGARI (RKP NAGARI) - Surya Ningsih; Silsila Asri (Ensiklopedia Social Review, 2021)
Every year the nagari government prepares a work plan before the determination of the APBNagari. The process of preparing this planning document is usually based on the Minister of Home Affairs Regulation No. 114/2014, but in 2020 the Minister of Village Regulation No. 21/2020 regulates the same. There are differences in the process of preparing the RKP Desa regulated by the two regulations. The purpose of this paper is to see the impact of overlapping regulations in the preparation of the RKP Nagari in Lima Puluh Kota Regency. The method used in this research is descriptive qualitative. The results of the study indicate that there are 2 impacts of the overlapping regulations, First, the District Government of Lima Puluh Kota is slow in responding to the latest regulations so that the regent's regulations governing the Technical Guidelines for the Preparation of RPJM, RKP, and Implementation of Nagari Development Activities have not been revised so that the process the preparation of the RKP applied by the nagari varies, some are implemented according to the regent's regulations and some are in accordance with the village minister's regulations. Second, the emergence of internal disputes within the Nagari government because they are confused about implementing the process of preparing the Nagari RKP in accordance with the regulation of Permendagri No. 114/2014 or Village Minister Regulation No. 21/2020.Keywords: Village, Regulation, Development Planning